Location Domination Number of Sum of Graphs - Rajasekar, G.; Nagarajan, K.; Seenivasan, M. (International Journal of Engineering and Technology, 2018)
Locating dominating set is the subset  of the vertex set  which dominate and uniquely identify all vertices of the set . In this paper we formulated the apt method for finding the location domination number of sum of graphs  based on the nature of the graphs  and .